Food Insecurity Amid the COVID-19 Lockdowns in Nigeria: Do Impacts on Food Insecurity Persist After Lockdowns End? - Martinez, Elena (Curr Dev Nutr, 2021)
OBJECTIVES: In response to a rapid rise in COVID-19 cases in Nigeria in March and April 2020, governments in some states imposed lockdowns. While lockdowns may be crucial for disease prevention and control, they also disrupt food systems and economic activity and may have devastating impacts on vulnerable households. This study uses longitudinal data to examine trends in household food insecurity in Nigeria just after lockdowns were imposed and at multiple points later in 2020, and assesses the impacts of lockdowns in spring 2020 on household food insecurity. METHODS: This study utilizes data from the Nigerian General Household Survey 2018/19 and the first seven rounds of the LSMS-ISA National Longitudinal Panel Survey on COVID-19 collected between April-November 2020. We assess trends in household food insecurity, as measured by the Food Insecurity Experience Scale (FIES), before and during the COVID-19 pandemic and use a difference-in-difference design to estimate the impact of COVID-19 lockdowns on household food insecurity. RESULTS: Household food insecurity in Nigeria increased significantly between Jan/Feb 2019 and the first months of the COVID-19 pandemic in April/May 2020. As the pandemic continued, food insecurity decreased between April/May and November of 2020 for all items in the FIES yet remained significantly higher than before the pandemic began. Difference-in-difference models, however, suggest that the lockdowns that were imposed in some Nigerian states did not significantly increase household food insecurity. CONCLUSIONS: When lockdowns were imposed in response to COVID-19 outbreaks in early 2020, many researchers and policymakers worried that households in low- and middle-income countries, many of which rely on informal work and/or daily wages for their livelihoods, would be vulnerable to food insecurity and hunger. Still, lockdowns are a key public health strategy for slowing the spread of infectious disease. As we continue to address COVID-19 and prepare for new emerging infectious diseases, we must weigh the risks and benefits strategies such as lockdowns. These results will help policymakers understand how measures to prevent and control COVID-19 influence livelihoods during a prolonged public health crisis. FUNDING SOURCES: This study does not have any funding sources.